(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Autonomy and cognitive emotion regulation both are important aspects of adolescent years. Previous research also indicates that an individual’s cognitive emotion regulation (CER) and autonomy is correlated. The present study aimed to gain more insight into the relationship between autonomy and cognitive emotion regulation of Bangladeshi adolescents. Cross sectional survey design was used covering 100 adolescents having an age range of 12-15 years of age for data collection. Participants completed the questionnaires including a demographic questionnaire, adolescent autonomy questionnaire and cognitive emotion regulation questionnaire. Correlation analysis suggests that autonomy support showed an increase in the adaptive emotion regulation. Regression analysis models revealed that adolescent autonomy significantly explained 14.6% of variance for adaptive emotion regulation, and 4.6% of variance for less adaptive emotion regulation. Findings from the present study embodied that Bangladeshi adolescents use more adaptive cognitive regulation than maladaptive emotion regulation. These findings have implications for parents, primary caregivers, child psychologists, and other relevant professionals who are and will be working with children/ adolescents in helping them to learn and enhance their autonomy for their future and effective cognitive regulation of emotion. Dhaka Univ. J. Biol. Sci. 32(1): 57-64, 2023 (January)